Characterization of the complete chloroplast genome of the Pohlia nutans M211 from Antarctica - Jin, Qing (Mitochondrial DNA B Resour, 2020)
The Antarctic Pohlia nutans M211 complete chloroplast (cp) genome, sequenced using Illumina NovaSeq PE150, was 125,199 bp in length. It contained 19,836 bp of inverted repeat (IR) regions that separated a large single-copy region (LSC) of 86,738 bp and a small single-copy region (SSC) of 18,580 bp. The whole-genome encodes 132 genes (80 protein-coding genes, 36 tRNA genes, and 8 rRNA genes) and had 29.5% GC content. The M211 was congruent with Sanionia uncinata (KM111545.1) according to the Phylogenetic tree analyses.